The PRIAMO study: urinary dysfunction as a marker of disease progression in early Parkinson's disease. (20th April 2017) - Picillo, M.; Palladino, R.; Barone, P.; Erro, R.; Colosimo, C.; Marconi, R.; Morgante, L.; Antonini, A.; ,
Abstract : Background and purpose: New venues are currently being explored to predict disease progression in Parkinson's disease (PD), such as non‐motor subtypes and models merging motor and non‐motor symptoms (NMS). By involving a subgroup of 585 patients from the PRIAMO (Parkinson Disease Non‐motor Symptoms) study, the present 24‐month longitudinal prospective analysis aimed to demonstrate that urinary dysfunction is an early marker of higher motor and non‐motor burden as well as lower health‐related quality of life. Methods and results: Multivariable mixed‐effect logistic regression models controlling for demographic and clinical variables showed that the following NMS domains were associated with urinary dysfunction: gastrointestinal [odds ratio (OR) 2.57, 95% confidence interval (CI) 1.67–3.97, P < 0.001], cardiovascular (OR 2.22, 95% CI 1.18–4.17, P = 0.013), skin (OR 1.81, 95% CI 1.06–3.08, P = 0.029), sleep (OR 2.06, 95% CI 1.34–3.16, P = 0.001), pain (OR 1.85, 95% CI 1.21–2.83, P = 0.004), fatigue (OR 2.40, 95% CI 1.56–3.68, P < 0.001), apathy (OR 2.79, 95% CI 1.72–4.52, P < 0.001) and respiratory (OR 1.82, 95% CI 1.02–3.23, P = 0.039). Analysis also demonstrated that urinary dysfunction was associated with higher motor disability (coefficient 1.73, 95% CI 0.68–2.78, P = 0.001) and lower health‐related quality of life (coefficient −0.05, 95% CI −0.08 to −0.02, P < 0.001, and coefficient −3.49, 95% CI −5.21 to −1.77, P < 0.001) but not with more severe cognitive disability (coefficient −0.34, 95% CI −0.92 to 0.24, P = 0.251). Conclusions: This is the first prospective longitudinal study involving a large cohort of PD patients demonstrating the relevance of urinary dysfunction as an early marker of higher motor and non‐motor disability as well as lower health‐related quality of life. These findings support a role for urinary dysfunction as an early marker of more severe disease progression.